Engineering geological assessment and rock mass characterization of the Asmari formation (Zagros range) as large dam foundation rocks in southwestern Iran - Van Rooy, J.L. (Jan Louis) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.